Stem bark ethanolic extract of Pinus merkusii induces caspase 9-mediated apoptosis in HeLa cells - Agung Budianto Achmad; Annise Proboningrat; Arif Nur Muhammad Ansori; Amaq Fadholly; Siti Eliana Rochmi; Rinza Rahmawati Samsudin; Nanik Hidayatik; Gracia Angelina Hendarti; Shara Jayanti (Open Veterinary Journal, 2024)
Background: Cervical cancer is a severe concern for women throughout the world. This percentage of cancer incidence causes sufferers to die at a high rate. It is believed that the bark of the Pinus merkusii tree contains anti-cancer compounds that inhibit cervical cancer cell growth.